Práticas pedagógicas nos manuais didáticos (1938-1945) - Leite, Maria Adélia Clementino (2013)
The analyzes of the textbooks in Brazil are recent, and has been intensified by researchers because of its importance for the understanding of the school routine. Thus, textbooks bring significant aspects and able to reveal different information: the type of knowledge selected to compose the set of content to be taught in schools in different historical contexts, the most expressive content over others; ideologies present in provision of such content; methodological guidelines presented in these manuals, the role that authors play in society and the relationship of these with the practice of teaching. In this perspective, the present study aimed at analyzing ace discussions about the pedagogical practices in textbooks, directed the Normal Schools and Educational Institutes. To achieve this goal, we define some specific goals to this effect: understanding and describing the contents, methods and practice developed in textbooks. The research was methodologically carried out a survey of bibliographic sources, and we mention from the backs of authors such as theoretical Bittencourt (2004, 2010) and Chartier (1990). To perform the analysis we chose the textbooks Treaty of Pedagogy, Monsignor Pedro Anísio of (1955) and School Practices, Antonio D'Avila, in (1958), the works bring itself elements that guided the formation and practice teachers, highlighting theoretical concepts, suggestions for references to studies provided by various authors, laws, and guidelines for the development of educational practices, such as lesson plans, suggestions for application of evidence, studies on the various types of methods, among others.